Feasibility of fetal cardiac function and anatomy assessment by real-time spiral balanced steady-state free precession magnetic resonance imaging at 0.55T - Ye Tian; Jon Detterich; Jay D. Pruetz; Ecrin Yagiz; John C. Wood; Krishna S. Nayak (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: Background: Contemporary 0.55T magnetic resonance imaging (MRI) is promising for fetal MRI, due to the larger bore, reduced safety concerns, lower acoustic noise, and improved fast imaging capability. In this work, we explore improved fetal cardiovascular magnetic resonance (CMR) without relying on any synchronizing devices, prospective, or retrospective gating, to determine the feasibility of real-time MRI evaluation of fetal cardiac function as well as cardiac and great vessel anatomies by using spiral balanced steady-state free precession (bSSFP) at 0.55T. Methods: A real-time spiral bSSFP pulse sequence for fetal CMR was implemented and optimized on a 0.55T whole-body MRI. Fetal CMR was prospectively performed between May 2022 and August 2023. The protocol included (1) real-time images at standard cardiac views, for 10–20 s/view and 40–43.6 ms/frame and (2) 4–9 stacks of slices at standard cardiac views that each cover the whole heart, with 15–30 slices/stack, and 2–5 s/slice, at 320–349 ms/frame. Images were evaluated by a fetal cardiologist. Quantitative measurements of cardiothoracic area ratio and cardiac axis were compared with previous reports. Diagnostic accuracy was compared against postnatal echocardiographic findings. Results: Twenty-nine participants were enrolled for 32 CMR exams, with mean maternal age 33.6 ± 5.8 years (range 22–44 years) and mean gestational age 32.8 ± 3.9 weeks (range 23–38 weeks). The proposed sequence enabled evaluation of the fetal heart in <30 min in all cases (average 22 min). Real-time MRI allowed easy adjustment of scan plan, automatic whole-heart volumetric sweeping, and flexible choice of reconstruction temporal resolution. For key cardiac anatomic features, 60% (315/527) were delineated well. Mean cardiothoracic area ratio and cardiac axis were 0.27 ± 0.04 and 45.8 ± 7.8 degrees. Diagnostic agreement with postnatal echocardiographic findings was 84% (26/31). Conclusion: A spiral real-time bSSFP pulse sequence at 0.55T can provide both low-framerate and high-framerate fetal heart images without relying on maternal breath-hold, specialized gating devices, or cardiac gating. The low-framerate images offer high diagnostic quality structural evaluations of the fetal heart, while the high-framerate images capture fetal heart motion and may enable functional assessments.